2016
DOI: 10.5539/jfr.v5n2p23
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Calcium Chloride and Hydrocooling on Postharvest Quality of Selected Vegetables

Abstract: <p>Precooling and postharvest application of calcium chloride (CaCl<sub>2</sub>) on produce has positive effects in maintaining the produce quality during storage. However, there is variation in the response of the produce to different CaCl<sub>2 </sub>concentrations<sub>. </sub>As a result, there is need to establish optimal concentrations of calcium chloride that can extend postharvest life of targeted produce. Fresh good quality produce (tomatoes, carrots, courgette… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 25 publications
3
13
2
Order By: Relevance
“…(). On the other hand, the beta‐carotene content reported in this study (Table ) is higher compared to previous reports by Chepngeno, Owino, Kinyuru, and Nenguwo () and Msogoya, Majubwa, and Maerere () on African eggplants. This could suggest a wide variability in the beta‐carotene content among African eggplant accessions (Plazas et al., ).…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…(). On the other hand, the beta‐carotene content reported in this study (Table ) is higher compared to previous reports by Chepngeno, Owino, Kinyuru, and Nenguwo () and Msogoya, Majubwa, and Maerere () on African eggplants. This could suggest a wide variability in the beta‐carotene content among African eggplant accessions (Plazas et al., ).…”
Section: Discussioncontrasting
confidence: 88%
“…Studies have shown that most phenolic compounds are concentrated in the skin surface of fruits (Dadalı, Kılıç Apar, & Özbek, 2007 as reported by Mwende et al (2018). On the other hand, the betacarotene content reported in this study (Table 2) is higher compared to previous reports by Chepngeno, Owino, Kinyuru, and Nenguwo (2016) and Msogoya, Majubwa, and Maerere (2014) on African eggplants. This could suggest a wide variability in the beta-carotene content among African eggplant accessions (Plazas et al, 2014).…”
Section: Discussioncontrasting
confidence: 65%
“…Fruits at earlier stages (turning color) could have longer shelf life due to low physiological activity compared to later stages under ZECC condition. The antifungal application maintains firmness through 6% CaCl2, saving its quality attributes and further enhancing shelf life, similar to reports by Arthur et al and Chepngeno et al [3,14].…”
Section: Shelf Lifesupporting
confidence: 86%
“…On the other hand, Gonz alez Aguilar et al (2008) showed that the combination of HWT + antioxidant solution increased the synthesis of carotenoids in minimally processed mangos during the first days of cold storage, with the highest rate observed during ripening. By contrast, the combination of HWT and CaCl 2 in cold-stored papaya (Ay on- Reyna et al, 2015), carrots, and eggplants (Chepngeno et al, 2016) reduced the BC content.…”
Section: Discussionmentioning
confidence: 90%